Assessment of patient satisfaction level in the State University of Haiti Hospital and responsible factors: a cross-sectional mixed-methods study protocol - Hugins Millien; Thaïmye Joseph (BMJ Open)
Introduction Over the past few years, the healthcare industry has undergone a significant transformation where patients’ perceptions of healthcare have gained a huge importance in assessing quality. Considering that it is now highly competitive, their contentment is a vital aspect in improving performance. However, practitioners in developing countries have traditionally overlooked the importance of patient views in healthcare, and this neglect is particularly prevalent in low-resource settings such as the State University of Haiti Hospital. The aim of this study is to assess patient satisfaction and identify influencing factors.Methods and analysis We will conduct a mixed-methods cross-sectional survey at Haiti’s largest hospital centre from January to August 2024. First, patient satisfaction will be assessed using RAND Corporation’s 18-Item-Patient Satisfaction Questionnaire, a valid self-administered questionnaire with strong potential for use in different settings. It will be translated into Creole and then tested in a pilot study. Second, a qualitative study based on individual interviews will explore patients’ views on the care they have received. Data analysis will include descriptive statistics, χ2 tests, logistic regression and thematic analysis.Ethics and dissemination Ethical approval is granted from the Laboratoire Médecine Ethique et Société. Findings will be published in a corresponding peer-reviewed journal, shared with hospital staff and students. Social media posts, blog posts and conference debates will also be considered.